Soil Erosion and Silt Problems and the Role of Forestry in Soil Conservation - Gupta, A. C. (Indian Forester, 1957)
When a land starts developing fast from a primitive stage a planned development is necessary for its well-being, and this is particularly true of a hill area made up mostly of semi-crushed rocks and subject to very heavy rainfall. Such has been the case with the North Bengal hills and Sikkim where lie the catchments of many rivers. Nature had provided these areas with a great deal of rich forest which held the balance between the soil, the rivers and the elements, but with the start of development and advent of prosperity the population grew manifold; and before a realization had dawned on the administrators practically all forests in the areas more favourably situated got depleted, and the delicate soil was subjected to all forms of malpractices. The inevitable followed in course of years, and heavy soil erosion, the silting up of water courses and floods resulted. Now therefore arises a question of remedy, but remedy is difficult in the altered circumstances of human needs. Special slip forestry which is the only known effective means of restoration of soil equilibrium has perforce to be practised, but in order to keep the problem of eviction and rehabilitation of peasants to the minimum only such areas should be trreated under forestry as have completely gone out of hand, the rest being brought under conditional cultivation. The putting up of check dams in the waterways aimed at reducing the velocity of the flow is not considered wise until after sometime when the excessive soil erosion will have been brought under control, and thus the risk of the dams being completely buried removed.